The Evolution of Forest Restoration in Europe: A Synthesis for a Step Forward Based on National Expert Knowledge - Maitane Erdozain; Iciar Alberdi; Réka Aszalós; Kurt Bollmann; Vassilis Detsis; Jurij Diaci; Martina Đodan; Georgios Efthimiou; László Gálhidy; Marie Haase; Johanna Hoffmann; Delphine Jaymond; et al. (Current Forestry Reports, 2024)
Purpose of review We are amid a historical momentum encouraging forest restoration, yet the translation of ambitious targets into reality is hindered by poor documentation and understanding of the success and failure of past restoration efforts. This review aims to evaluate the ecological, social, political and economic characteristics of forest restoration across Europe, their development over time and key lessons learned to guide future restoration initiatives. The analysis is based on the synthesis of expert assessments from 18 European countries. Recent findings Early restoration initiatives in central and southern Europe were largely reactive to natural disasters or timber shortages, and while effective in erosion control and timber production, their ecological benefits were often limited due to monoculture plantations and short-rotation systems. Geopolitical crises intensified timber production, with nationalized and centrally managed forests in several countries, but often at the cost of biodiversity. Since the 1990s, a shift toward multifunctionality has emerged driven by the convergence of environmental, social, political and economic events. Summary Forest restoration in Europe has transitioned from disaster reduction and production-driven efforts to a more multifunctional approach that promotes biodiversity. Changes have been driven by a combination of environmental (e.g., catastrophic consequences following natural disasters), political (e.g., wars, forest nationalization and management centralization), legal (e.g., strict and ambitious national and international policies), social (e.g., rural abandonment and changes in societal values) and economic (e.g., new funding mechanisms or market fluctuations) events. Despite the development, conflicting goals, insufficient funding, climate change and short-term thinking persist as key barriers.